Parallel orchestration and deployment system for scalable heterogeneous service function chain supporting polymorphic network - Hao CHEN; Yuan YANG; Mingwei XU; Dan PEI; Yilin YOU (Tongxin xuebao)
Aiming at the problem of second-level service function chain orchestration and deployment in the polymorphic data center with the scale of 10 000 servers, a scalable heterogeneous SFC parallel orchestration and deployment (SHOD) system was proposed.The scale-out orchestration time of service chain was reduced to seconds by partitioning the data center and adopting a parallel orchestrator design that minimizes resource usage.Using a mediator design model that satisfies the single-responsibility principle, the heterogeneous equipment scalable orchestration and deployment were realized as well as service function chain building chain.Experimental results show that in a data center with 10 000 servers, the scale-out orchestration time of SHOD system is reduced to 1 12 of the existing system-Daisy, while only 1.5 times CPU utilization overhead is introduced.